Corn Response to POST-Applied HPPD-Inhibitor Based Premix Herbicides with In-Furrow and Foliar-Applied Insecticides. (March 2015) - Steckel, Lawrence E.; Stewart, Scott D.; Steckel, Sandy
Abstract : In recent years injury has been reported in numerous Tennessee corn fields treated with an organophosphate (OP) insecticide and either a mesotrione- or tembotrione-based herbicide premix. Research was conducted with the objective to determine if corn treated with an in-furrow application of chlorpyrifos or a foliar application of chlorpyrifos or bifenthrin, or a combination of in-furrow and foliar treatment, would be more predisposed to injury when either a premix of S -metolachlor, mesotrione, and glyphosate (meso premix) or a premix of tembotrione plus thiencarbazone (tembo premix) was applied. The main effects of insecticide or herbicide, the two-way interaction of insecticide by herbicide, and the three-way interaction of herbicide by insecticide by application type of insecticide were all significant for injury as well as yield. When chlorpyrifos was used both in-furrow and foliarly on corn treated with the tembo premix, injury was increased to 56% and yield was reduced 58% compared with corn that had not been treated with that insecticide. This use pattern of chlorpyrifos utilized in-furrow followed by chlorpyrifos applied foliarly with the tembo premix essentially doubled the injury (29 to 56%) and increased yield loss from 41% where chlorpyrifos was only utilized foliarly to 49% when chlorpyrifos was applied in-furrow and foliarly. Corn injury was negligible (< 6%) and yield was similar where the meso premix was examined in combination of both types of insecticide applications. This study clearly demonstrated the phytotoxic interaction between these two herbicide premixes and the OP insecticide chlorpyrifos. Therefore, growers need to be mindful of which herbicides are utilized when OP insecticides are used for insect management.